Robust Lithium–Sulfur Batteries Enabled by Highly Conductive WSe2‐Based Superlattices with Tunable Interlayer Space. (13th March 2022) - Zhang, Chaoqi; Fei, Ban; Yang, Dawei; Zhan, Hongbing; Wang, Jiaao; Diao, Jiefeng; Li, Junshan; Henkelman, Graeme; Cai, Daoping; Biendicho, Jordi Jacas; Morante, Joan Ramon; Cabot, Andreu
Abstract: Superlattices are rising stars on the horizon of energy storage and conversion, bringing new functionalities; however, their complex synthesis limits their large‐scale production and application. Herein, a simple solution‐based method is reported to produce organic–inorganic superlattices and demonstrate that the pyrolysis of the organic compound enables tuning their interlayer space. This strategy is exemplified here by combining polyvinyl pyrrolidone (PVP) with WSe2 within PVP/WSe2 superlattices. The annealing of such heterostructures results in N‐doped graphene/WSe2 (NG/WSe2 ) superlattices with a continuously adjustable interlayer space in the range from 10.4 to 21 Å. Such NG/WSe2 superlattices show a metallic electronic character with outstanding electrical conductivities. Both experimental results and theoretical calculations further demonstrate that these superlattices are excellent sulfur hosts at the cathode of lithium–sulfur batteries (LSB), being able to effectively reduce the lithium polysulfide shuttle effect by dual‐adsorption sites and accelerating the sluggish Li–S reaction kinetics. Consequently, S@NG/WSe2 electrodes enable LSBs characterized by high sulfur usages, superior rate performance, and outstanding cycling stability, even at high sulfur loadings, lean electrolyte conditions, and at the pouch cell level. Overall, this work not only establishes a cost‐effective strategy to produce artificial superlattice materials but also pioneers their application in the field of LSBs. Abstract : N‐doped graphene/WSe2 (NG/WSe2 ) superlattice obtained by a cost‐effective synthetic strategy is used as a sulfur host to regulate lithium polysulfide (LiPS) conversion reaction. The increased interlayer spacing (1.04 nm) and enhanced conductivity guarantee the ion and electron transfer in Li–S reaction process, and the heterogeneous interface probes strong lithio/sulfiphilic dual‐adsorption sites to confine the LiPS shuttle effect. Consequently, robust lithium–sulfur batteries are obtained.